If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u = 2u + -16 Reorder the terms: 4u = -16 + 2u Solving 4u = -16 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 4u + -2u = -16 + 2u + -2u Combine like terms: 4u + -2u = 2u 2u = -16 + 2u + -2u Combine like terms: 2u + -2u = 0 2u = -16 + 0 2u = -16 Divide each side by '2'. u = -8 Simplifying u = -8
| 1.21x=9.68 | | -9x+12+4(3x-3)=7(x-2)-4+14 | | 21=5w-14 | | 462=42t+4 | | 5x+4(100-x)=100 | | 70(3x+10)=180 | | 70(3x+10)= | | 6y+4x= | | 48=2v+12 | | 7+3x=0.5(14+6x) | | z/7-9=3 | | t-17=20 | | 2x+5+2x+3x= | | 4(x-1)=-5(x+3)+32 | | -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= |